2019
DOI: 10.3390/jcm8122181
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microperimetry: A Useful Tool for Detecting Insulin Resistance-Related Cognitive Impairment in Morbid Obesity

Abstract: Background: There is clear association between type 2 diabetes (T2D) and cognitive decline. Retinal microperimetry is a useful tool for detecting cognitive impairment in T2D. Morbid obesity (MO) has been associated with cognitive impairment. Insulin resistance (IR) seems a major determinant, but the data are unclear. The aim of this study was to evaluate the cognitive impairment in MO as well as the utility of retinal microperimetry in identifying these alterations. Methods: In total, 50 consecutive patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Additionally, attention and delayed recall, which were significantly correlated in our study with gaze-fixation parameters, depend mainly on the default brain network and the white-matter connections between the dorsolateral and prefrontal cortex and inferior and superior parietal lobules [ 15 , 16 ]. In support of this data, our group previously showed that gaze fixation was impaired in young patients with obesity and significantly correlated with cognitive function, in particular with attention span, while retinal sensitivity was not altered and did not correlate with the neurocognitive scores [ 13 ]. These results suggest that alterations in white matter connectivity are more subtle and occur earlier than neurodegeneration in the visual pathway, thus explaining why the alterations in both gaze fixation and cognitive domains (attention and delayed recall) could already be seen at 12 month follow-up, while retinal sensitivity remained unchanged.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Additionally, attention and delayed recall, which were significantly correlated in our study with gaze-fixation parameters, depend mainly on the default brain network and the white-matter connections between the dorsolateral and prefrontal cortex and inferior and superior parietal lobules [ 15 , 16 ]. In support of this data, our group previously showed that gaze fixation was impaired in young patients with obesity and significantly correlated with cognitive function, in particular with attention span, while retinal sensitivity was not altered and did not correlate with the neurocognitive scores [ 13 ]. These results suggest that alterations in white matter connectivity are more subtle and occur earlier than neurodegeneration in the visual pathway, thus explaining why the alterations in both gaze fixation and cognitive domains (attention and delayed recall) could already be seen at 12 month follow-up, while retinal sensitivity remained unchanged.…”
Section: Discussionsupporting
confidence: 56%
“…The brain structures that play an essential role in gaze fixation are the superior colliculus and parietal and frontal cortex. [ 13 ]. It should be noted that the retina has several types of ganglion cells, most of them directly connected to the geniculate body of the visual pathway, but others are connected directly to the superior colliculus [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal sensibility relies on the retina and the neural pathway of vision, which includes the geniculate body and correlated with grey matter volumes in brain MRI in T2D patients with MCI and AD but not white matter ( 30 ), suggesting that could be a marker of neurodegeneration. On the other hand, gaze fixation depends on the complex white matter network ( 37 ).…”
Section: New Emerging Methods For Screening and Monitoring Of Cogniti...mentioning
confidence: 99%
“…Additionally, it is non-invasive, repeatable, can be performed independently of the education level, and can provide detailed information about the speci c areas of the retina that are affected by disease. It has been described that the combination of retinal sensitivity and gaze xation parameters correlate with brain imaging ndings (MRI and PET) and can identify patients with mild cognitive impairment (MCI) and dementia in people with type 2 diabetes (T2D) 13 , and people with insulin-resistant morbid obesity 14 . According to these studies, gaze xation appears to be a more subtle biomarker, as it depends on the complex white matter network in the brain and is affected by attention and working memory, while retinal sensitivity relies on the retina and the neural pathway of vision 13 .…”
Section: Introductionmentioning
confidence: 99%